Evaluation of Knee Joint Injuries with Magnetic Resonance Imaging (MRI) and Correlation with Arthroscopy - Muhammad Afrasiyab Javed Khan, Mohib Ullah Khan, Zia Ullah, Asad Ullah, Jaweria Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
One of the most frequent issues humans have had to deal with from the beginning of time is a knee injury. Knee injuries caused by a variety of diseases, from acute to degenerative, can affect the articular cartilage. The trauma, infection, or inflammation caused this injury. In these circumstances, a full clinical examination is not possible since the patients are in too much pain to cooperate. Then non-invasive multiplanar imaging and MRI come into play. The objective of the current study was to assess knee joint injuries using MRI and correlate those findings with arthroscopy. A total number of 225 participants were involved in this study, among them, 175 had issues with a knee injury. The patients referred with a history of knee injury were imaged with a 1.5 Tesla MRI machine. Most patients were between the ages of 35-40 years. The most frequent injuries found in the study were bone contusions, joint effusions, anterior cruciate ligament tears, and tears of the posterior horn of the medial meniscus. The accuracy percentage of ACL, PCL, LCL and MCL were 93, 100, 94.02 and 91.34%, respectively. Due to its great soft tissue contrast resolution and multiplanar imaging capabilities, magnetic resonance imaging (MRI) is a superior non-invasive investigative method for knee injuries. This allows for the most thorough evaluation of a variety of soft tissue knee joint problems. Keywords: Knee joint injury; Magnetic resonance imaging; Arthroscopy;